Paradigma Teoretis dalam Psikologi: Landasan Filsafati, Peluang, dan Limitasi dalam Penelitian dan Praktik Psikologi: Theoretical Paradigms in Psychology: Philosophical Foundations, Opportunities, and Limitations in Psychological Research and Practice - Rizkiyani, Fanny; Selian, Sri Nurhayati (Jurnal Filsafat Indonesia, 2025)
Behaviorism, psychoanalysis, and humanism are three distinct theoretical paradigms in psychology. Each paradigm provides valuable insights and has important implications for psychological research and practice. Understanding the philosophical differences between the three is essential to apply them appropriately both in research and practice. This study aims to examine the ontological and epistemological foundations of the three paradigms, as well as their opportunities and limitations in psychological research and practice. The methodology used is a literature review. The results of this study describe the ontological assumptions of behaviorism, which is based on materialism and environmental determinism; psychoanalysis, which is rooted in transcendental idealism and psychic determinism; and humanism, which emphasizes free will and subjective experience. In terms of epistemology, this study explains that behaviorism adopts an empiricist approach (logical positivism), humanism uses phenomenology, and psychoanalysis uses hermeneutics or epistemological modesty. The differences in the three paradigms' philosophical foundations have implications for each paradigm's opportunities and limitations in psychological research and practice.